Utilization of freeze-dried lablab and lumot as feeds for sex-reversed Tilapia mossambica fry. - Amparado, Christina (Iloilo City UPHSI, 2006)
Tilapia is one of the most important fish cultured in the Philippines. It constitutes a large bulk of the Philippines' income for livelihood. Various approaches and economical techniques of improving the tilapia culture in the Philippines were undertaken by researchers focusing mostly in their feeds; such studies include freeze-drying in preserving the shelf-life of the processed materials for future use. This involves the use of the freeze-dried lablab and lumot to determine the growth and survival rates of the T. mossambica fry. A study on the utilization of freeze-dried lablab and lumot as feeds for sex-reversed Tilapia mossambica fry was conducted for six weeks. The efficacy of the different feeds were assessed using the growth rate and survival of the Tilapia fry. Tilapia fed with commercial pellets had significantly higher growth and survival rates than the other treatments, which were not significantly different from each other at 95% confidence interval. This can be attributed to the complete nutritional composition found in commercial pellets which can sustain the needs of the tilapia, unlike lumot and lablab that lack the necessary nutritional requirements for growth and survival.
Research II : Research Manuscripts
Keywords: Lablab; Lumot